Simulation study on the effect of dielectrophoresis force on a separation of platelet from blood cell in a 3D mini channel - Nur Tantiyani Ali Othman,; Lee, C. S. (Penerbit Universiti Kebangsaan Malaysia, 2021)
In recent years, separation of platelet from a blood cell received growing attention due to its usages for blood disorders or any disease treatment. However, the conventional separation techniques have some constraint due to its limitation to separate the cells with similar properties, costly, requires longer processing time, and less data accuracy. Thus, under the effect of a uniform electric field, a dielectrophoretic (DEP) force was applied as its ability to separate on a similar diameter size of cells, has lower cost, and requires only a small volume of sample. In this study, a 3D mini channel model with a Y-shape was developed using AutoCAD® and the velocity profile distribution was observed using ANSYS© Fluent version 19.1. Three parameters were observed at various an electric field intensity; E=±1 to ±5 V/mm, an electric field frequency, f=1 kHz to 1 MHz and a particle diameter; d=1.3 to 2.0μm. The results show the velocity was increased as the higher of electric field intensity and larger particle diameter. Besides, the DEP force was increased as the higher electric field intensity was charged for all tested frequencies. As well, as the higher the electric field intensity charged and the larger the particle diameter, the stronger of the DEP force. It can be concluded that the DEP force at d=2.0μm and E=5 V/mm was the optimum conditions and obtained the highest result among all the tested parameters. Under these optimum conditions, it shows the DEP force can separate the platelet from the blood cells.